2015
DOI: 10.1007/s12350-015-0217-1
|View full text |Cite
|
Sign up to set email alerts
|

ImageGuide™ Update

Abstract: TM-continues to make exceptional progress toward implementation this summer. The culmination of this historic journey has been achieved by involving a broad spectrum of experts in the fields of nuclear cardiac imaging, data registries using outcomes-based research, our industry partners, and, most importantly, ASNC membership. This initiative is the result of a shared vision of what nuclear cardiology's future role will be in impacting patient management. Focused registries were initially considered 15 years a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
(7 reference statements)
0
8
0
Order By: Relevance
“…The sustainability of our quality improvement initiative and its adaptability to other practice settings remain to be seen. The ImageGuideEcho registry 11,12 could serve as an important resource for facilitating continuous quality improvement in the performance of comprehensive TEE. Further studies investigating the impact of the performance of comprehensive TEE on health care costs and clinical outcomes are needed.…”
Section: To the Editormentioning
confidence: 99%
“…The sustainability of our quality improvement initiative and its adaptability to other practice settings remain to be seen. The ImageGuideEcho registry 11,12 could serve as an important resource for facilitating continuous quality improvement in the performance of comprehensive TEE. Further studies investigating the impact of the performance of comprehensive TEE on health care costs and clinical outcomes are needed.…”
Section: To the Editormentioning
confidence: 99%
“…There are initiatives in the cardiology community which can help in this respect. For example, in nuclear cardiology community, the American Society of Nuclear Cardiology has led efforts to gather all relevant clinical data via the ImageGuide registry [122]. Reporting software vendors are cooperating and will be providing appropriate interfaces to hospital systems to collect and transmit such data linking these with the images.…”
Section: Issues and Potential Pitfallsmentioning
confidence: 99%
“…It has been shown that machine learning algorithms derived from integrating clinical, perfusion, and functional data elements for diagnosis of obstructive CAD yield results similar to or better than those obtained by experienced readers. 55 Furthermore, machine learning applications, integrating clinical, ECG, exercise, hemodynamic, defect quantification, and ancillary imaging data provide a patient-specific estimate of likelihood of early revascularization and allcause mortality, thus aiding in individualized decisionmaking in a way the human brain cannot do. 53,56 Machine learning algorithms are a natural complement to nuclear cardiology analyses packages and structured reporting software, from which multi-faceted data can be derived to generate risk estimates factored in DSTs and patient-centered decision guidance.…”
Section: Machine Learningmentioning
confidence: 99%
“…Thus, data from each study can be easily submitted from the laboratory to the ImageGuide TM Registry, which in turn tracks and publicly reports, in real-time, indicators of excellence in radionuclide imaging, including crucial reporting measures. 16,54,55 Such integration provides a constant quality improvement feedback loop for ever-improving report quality and patient care. 57 The ImageGuide TM Registry is a Qualified Clinical Data Registry (QCDR) through which participating physicians can receive CMS reimbursement credits for participating in a Physician Quality Reporting System (PQRS).…”
Section: Registries and Public Reportingmentioning
confidence: 99%